Proceedings of the 17th IAARC/CIB/IEEE/IFAC/IFR International Symposium on Automation and Robotics in Construction 2000
DOI: 10.22260/isarc2000/0048
|View full text |Cite
|
Sign up to set email alerts
|

Open Issues and Future Possibilities in the EU Construction Automation

Abstract: Abstract:The open issues and the main barriers to introducing automation in the construction industry are analyzed. Future possibilities of massive introduction of automation are also analyzed. These analysis are focusing in the house-building construction in the European Union (EU). The level of advances and comparative study with others industrial sectors show that more effort are needed. In this way two examples are presented: bricklayer robots and modules assembly robots, focusing in the main barriers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Warsawzki and Navon [3] lamented the failure of the diffusion of robotics in the 1990s in spite of early promising research efforts and cited the following reasons to be its cause: current building and construction practices not being amenable to performance by robots; insufficient development of construction robots to deal with site conditions; the lack of economic justification of robots; and the managerial environment in the construction industry. This sentiment was shared by Balaguer [11] who concluded that the industry still operates by the same philosophy as from the pre-industrial era, the only major advancements being the use of motors to apply force and the replacement of human and animal power with machines to do the same work while manual control, visual feedback, human operators, etc. still play a vital role in construction.…”
Section: Current State Of the Art And Trends In Construction Automationmentioning
confidence: 99%
“…Warsawzki and Navon [3] lamented the failure of the diffusion of robotics in the 1990s in spite of early promising research efforts and cited the following reasons to be its cause: current building and construction practices not being amenable to performance by robots; insufficient development of construction robots to deal with site conditions; the lack of economic justification of robots; and the managerial environment in the construction industry. This sentiment was shared by Balaguer [11] who concluded that the industry still operates by the same philosophy as from the pre-industrial era, the only major advancements being the use of motors to apply force and the replacement of human and animal power with machines to do the same work while manual control, visual feedback, human operators, etc. still play a vital role in construction.…”
Section: Current State Of the Art And Trends In Construction Automationmentioning
confidence: 99%
“…Automation of tasks may be included within a larger system or be carried out by only one machine. In this case, these machines areconsidered construction robots [3].…”
Section: Automatization and Robotization In Constructionmentioning
confidence: 99%
“…The significant change that this work wants to introduce is the user-in-the-loop philosophy in building construction, from design to the final cycle of life of the building [1]. In this way, the user can take part in all the stages of the process to get a final product according to his/here preferences.…”
Section: User-in-the-loopmentioning
confidence: 99%